Mean-field and linear regime approach to magnetic hyperthermia of core–shell nanoparticles: can tiny nanostructures fight cancer?. Issue 15 (5th April 2016) - Carrião, Marcus S.; Bakuzis, Andris F.
Abstract : A novel analytical model indicates how to tune the properties of small nanoparticles for clinical cancer magnetic hyperthermia. Abstract : The phenomenon of heat dissipation by magnetic materials interacting with an alternating magnetic field, known as magnetic hyperthermia, is an emergent and promising therapy for many diseases, mainly cancer. Here, a magnetic hyperthermia model for core–shell nanoparticles is developed. The theoretical calculation, different from previous models, highlights the importance of heterogeneity by identifying the role of surface and core spins on nanoparticle heat generation. We found that the most efficient nanoparticles should be obtained by selecting materials to reduce the surface to core damping factor ratio, increasing the interface exchange parameter and tuning the surface to core anisotropy ratio for each material combination. From our results we propose a novel heat-based hyperthermia strategy with the focus on improving the heating efficiency of small sized nanoparticles instead of larger ones. This approach might have important implications for cancer treatment and could help improving clinical efficacy.